Сімейні фермерські господарства: тенденції розвитку в світі та сучасний напрям господарювання в Україні - Нестеренко, Ю. О.; Nesterenko, Y. (КНТУ, 2015)
Розглянуто тенденції розвитку сімейних фермерських господарств у світі та пріоритети його регулювання. Проаналізовано внесок господарств населення України у розвиток сільськогосподарського виробництва, становище та розвиток даного напряму господарювання в Україні. Проведено аналіз досліджень та публікацій з даної проблематики та обґрунтовані перспективні напрями економічних досліджень в цій сфері. Досліджено напрями удосконалення законодавчого регулювання діяльності сімейних фермерських господарств в Україні. The objective of this study is to highlight the importance of family farms to the world economy and the state of its implementation of the economic activity in Ukraine. Tendencies of development of family farms in the world and the priorities of its regulation were considered. It was established that, 500 million out of 570 million farms that exist - are family farms, they account for about 98% of the world's agricultural land, and they produce more than 50% of agricultural production. It was proved that the Food and Agriculture Organization of UN refers to family farms all kinds of family agricultural activities, covering several areas of rural development. It was determined that the "analog" to world family farms in Ukraine are the personal farms, which occupy an important place in agricultural production in Ukraine. We proved that their legal status and actual conditions of substantially different from the foreign practice etc.
Family Farms: World Trends and Modern Way of Economic Activity in Ukraine
Keywords: сімейне фермерське господарство; господарства населення; сільське господарство; законодавче регулювання; family farms; households; agriculture; legal regulation